Hemodynamic Scaling of Task-Induced Signal Changes in Tumor Subjects - Qiu, Tianming; Hameed, N. U. Farrukh; Lin, Ching-Po; Biswal, Bharat B.; Wu, Jinsong (Frontiers in Human Neuroscience, 2020)
Background: FMRI signal measurements comprise both neural and vascular changes. The amplitude of signal changes during stimulus presentation are affected by the underlying neural function and the underlying hemodynamic response. In this study, we performed motor and/or language fMRI in 21 subjects with brain tumor. Methods: A breath-hold task was performed in these subjects to obtain the hemodynamic response changes independent of neural changes. The task activation signals were calibrated on a voxel wise basis for all the subjects. Direct cortical stimulation was used to verify the scaled results of task-based fMRI. Results: After scaling for the hemodynamic response function (HRF) on a voxel wise basis, the spatial extent of the scaled activation was more clustered together and appeared to minimize false positives. Similarly, accounting for the underlying canonical HRF, the percentage increase of active voxels after scaling had lower standard non-deviation suggesting that the activation response across voxels were more similar. Conclusion: Although preliminary in nature, this study suggests that the variation in hemodynamic changes can be calibrated using breath-hold in brain tumor subjects and can also be used for other clinical cases where the underlying HRF has been altered.